2011
DOI: 10.1371/journal.pone.0021852
|View full text |Cite
|
Sign up to set email alerts
|

Toward A Brain-Based Theory of Beauty

Abstract: We wanted to learn whether activity in the same area(s) of the brain correlate with the experience of beauty derived from different sources. 21 subjects took part in a brain-scanning experiment using functional magnetic resonance imaging. Prior to the experiment, they viewed pictures of paintings and listened to musical excerpts, both of which they rated on a scale of 1–9, with 9 being the most beautiful. This allowed us to select three sets of stimuli–beautiful, indifferent and ugly–which subjects viewed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
336
3
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 381 publications
(359 citation statements)
references
References 31 publications
12
336
3
8
Order By: Relevance
“…As a notable exception, the activation of the dopaminergic reward system during listening to pleasurable music (presumably including pleasurable sad music) has been suggested to be driven by the degree to which musical events match implicit predictions about how music unfolds in time [108], akin to the musical expectancy mechanism proposed by Juslin and Västfjäll [22] and the ideas of Huron [109] and Meyer [110]. Based on neuroimaging evidence suggesting that music can engage the putative human have been taken in the context of both music [112] and other art forms [113].…”
Section: Neural Correlates Of Music-induced Sadness and Pleasurementioning
confidence: 99%
“…As a notable exception, the activation of the dopaminergic reward system during listening to pleasurable music (presumably including pleasurable sad music) has been suggested to be driven by the degree to which musical events match implicit predictions about how music unfolds in time [108], akin to the musical expectancy mechanism proposed by Juslin and Västfjäll [22] and the ideas of Huron [109] and Meyer [110]. Based on neuroimaging evidence suggesting that music can engage the putative human have been taken in the context of both music [112] and other art forms [113].…”
Section: Neural Correlates Of Music-induced Sadness and Pleasurementioning
confidence: 99%
“…Brain imaging research on neuroesthetic shows that the core neural networks underlying pleasure evoked by beauty are likely to engage the same neural structures that mediate emotions, and, in particular, the reward systems (Cela-Conde et al, 2004;Ishizu and Zeki, 2011;Kawabata and Zeki, 2004;Marzi and Viggiano, 2010;Vartanian and Goel, 2004;Wiesmann and Ishiai, 2008;Chatterjee et al, 2009). Thus, it has been found that the esthetic experience involves a widely distributed circuit with greater activation for beautiful stimuli in anterior cingulate gyrus, dorsolateral and medial frontal cortices (Berridge and Kringelbach, 2008;Breiter et al, 2001;Di Dio et al, 2011;Kirk et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the former, a large body of literature in neuroaesthetics has demonstrated that aesthetic judgments activate a distributed neural network (30), including the brain's reward and affective circuitry (31)(32)(33)(34)(35)(36). Indeed, based on the results of the largest meta-analysis of neuroimaging studies of aesthetic appraisal to date, Brown et al defined a "core circuit for aesthetic processing" (37).…”
mentioning
confidence: 99%